Integrasi P3SPS dan Etika Komunikasi Islam: Analisis Kaidah Al-Qaulan sebagai Filter Moral dalam Regulasi Penyiaran di Indonesia: Integrasi P3SPS dan Etika Komunikasi Islam: Analisis Kaidah Al-Qaulan sebagai Filter Moral dalam Regulasi Penyiaran di Indonesia - Muh. Arsil; Nurasisah; Alfiansyah Anwar; Iskandar (Communication and Islamic Broadcasting Studies IAIN Parepare, 2026)
The development of the broadcasting industry in Indonesia has created challenges arising from the tension between media commercial interests and moral responsibility in delivering information to the public. Ethical violations such as privacy exploitation, content sensationalism, and the neglect of child protection indicate that formal regulations alone are insufficient to ensure ethical broadcasting practices. This study aims to analyze the synchronization between the Broadcasting Code of Conduct and Broadcast Program Standards (P3SPS) and the principles of Islamic communication ethics, particularly the concept of Al-Qaulan, as a moral filter within broadcasting regulations in Indonesia. This research employs a descriptive qualitative method with a library research approach. Data were collected from Law Number 32 of 2002 concerning Broadcasting, P3SPS, Qur’anic verses related to communication, and relevant academic literature. The findings reveal that P3SPS provisions concerning privacy protection, politeness, child protection, and information accuracy are substantially aligned with the principles of Al-Qaulan, namely Qaulan Sadidan, Balighan, Ma’rufan, Kariman, Layyinan, Maysuran, and Tsaqilan. The study concludes that the internalization of the Seven Qaulan principles can strengthen the effectiveness of broadcasting regulations by fostering moral awareness among media practitioners, thereby creating a more ethical, humane, and socially beneficial broadcasting ecosystem.